Evolution equation for entanglement of multiqubit systems - Siomau, Michael; Fritzsche, Stephan (Physical review. A, Atomic, molecular, and optical physics, 2010)
We discuss entanglement evolution of a multiqubit system in which one of its qubits is subjected to a general noisy channel. For such a system, an evolution equation of entanglement for a lower bound for multiqubit concurrence is derived. Using this evolution equation, the entanglement dynamics of an initially mixed three-qubit state composed of a Greenberger-Horne-Zeilinger (GHZ) and a W state is analyzed if one of the qubits is affected by a phase, an amplitude, or a generalized amplitude damping channel.
Gesehen am 08.08.2023